#TITLE_ALTERNATIVE# - Wardana NIM. 28195068, Hendriarta
Abstract: PT. Pindad (Persero) was founded earlier as a military instalation to became a state owned company with broader business spectrum including non-military businesses. Local government market, as the company's captive market seemed to be very restricted and too much influenced by the national economic situation. Meanwhile there are some opportunity within private sector or export market as long as company could achieve some technological andlor price leadership as competence. In order to survive and grow in the free tarde and free competition era, company should be able to gain some appropriate profit through increasing revenue and minimizing cost, as well as having a good looking financial report in order to be credible on the eyes of the fund resources. To increase revenue could be done by following market penetration, product development, market development and business diversification strategies. By having such an assets, with was more aimed to achieve national strategic consideration, and overemployment with under-qualification that the company suffer untill around 1995-1996, the fixed cost (generated from depreciation/ammortization and general expenses) that company should bear forcing company to an unprofitable situation even sales revenue has been increased. By the mentioned reason, it was proposed to do an act of re-evaluation of company's assets along with the capital structure, in order to minimize the depreciation/ammortization fixed cost, to meet a competitive machine hour rate. Another kind of proposal to minimize fixed cost is through rationalization of company's personnel. By only doing each one of those proposals, when the yearly revenue declined by 25% from the optimistic target, company will still facing possibilities of not able to gain profits even until! the year of 2000. When the two mentioned type of proposals is done simultaniously, the company will have a possibility to gain profits even the yearly revenue is 50% declined from the optimistic target.